# 2h-8=h+17

### 13 Answers | Add Yours

Here's what you need to do in order to solve for "h."

First, you need to get all the h's on one side of the equation. To do that, you get rid of the h from the right side of the equation. That is done by subtracting h (and you have to do it to both sides of the equation).

So that gives you (2h-h)-8=(h-h) + 17 which comes out to

h-8 = 17

So now to solve for h, you have to get all the numbers on the right side of the equation. To do that, you add 8 to both sides (so that there is no longer a number on the left).

That gives you h = 17+8

So h = 25

2h-h=17+8

h=25

2h-8=h+17

h is the unknown variable here therefore in order to find out the value of h, it must be isolated,

2h - 8 = h + 17

2h - 8 - h = h + 17 -h (subtract h from both sides)

h - 8 + 8 = 17 + 8 (add 8 to both sides)

**h = 25 Answer.**

Input this value in the above equation to verify it.

**Solve** 2h - 8 = h + 17

2h-8=h+17 **Equation **

**Subtract h from both sides**

**Add 8 on both sides**

**Answer**

2h - 8 = h + 17

First subtract " h " on both sides, this way the " h " variables will be on the same side

By subtracting, your equation should look like

**h - 8 = 17 ** Now, Add 8 on both sides

By adding, your equation should look like

**h = 25 **which is your answer

2h-8=h+17

h-8=17 subtract h from both sides

h=25 add 8 to both sides

2h-8=h+17

you first try to get all unkown variables to one side

so subtract h from both sides

iit will give you

h-8=17

then add 8 to both sides to give you the value of 17

h=25.

To solve for h you need the terms on one side

2h-8=h+17

2h-h=17+8

h=25

2h-8=h+17

move the like terms to the same side

2h-h = 17+8

h=25

2h-8=h+17

Isolate variables

2h - h = 17 + 8

h = 25

2h-8=h+17 add 8 on both side

2h-8+8=h+17+8

2h=h+25 subtract h on both side

2h-h=25

1h=25

h=25

2h-8=h=17

+8 +8

0 25

2h = 25

2/2 = 25/2

h=12.5

2h+h=17-8

3h=9

divide eachside by 3 h =3